(untitled) (World Science, 2019)
Atrial fibrillation and its associated complications, such as ischemic stroke and systemic thromboembolism, remain as an urgent problem of today’s medicine. For the patients who are diagnosed by atrial fibrillation, an anticoagulant drug therapy is necessary. The main goal of our research was to study the rheological parameters in patients diagnosed with a permanent form of arrhythmia, namely to evaluated erythrocytes aggregation, eritrocytes membranes deformiability, plasma viscosity. In addition, we were interested in the effect of a direct inhibitor of micronized factor Xa - Xarelto on hemorheology to determine which hemorheologycal parameters play a primary role in the regulation of blood flow and how are provided the therapeutical effects of the medicine.